2016
DOI: 10.1083/jcb.201508106
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic formation of ER–PM junctions presents a lipid phosphatase to regulate phosphoinositides

Abstract: Abbreviations used in this paper: FRET, Förster resonance energy transfer; Oxo-M, oxotremorine M; PI, phosphatidylinositol; PIP, phosphatidylinositol phosphate; PM, plasma membrane; PS, phosphatidylserine; SCG, superior cervical ganglion; SOCE, store-operated calcium entry; TIRF, total internal reflection fluorescence; UHP LC/MS, ultrahigh-performance liquid chromatography coupled with mass spectrometry; VSP, voltage-sensing 5-phosphatase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
102
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(105 citation statements)
references
References 68 publications
(134 reference statements)
2
102
0
1
Order By: Relevance
“…Surprisingly, transformed cell lines in culture, even though they are mammalian, have diminished 38:4 in their phosphoinositides. We showed this here for nearly confluent CHO and tsA201 cells (both having 36:1 and 36:2) [38], and a similar “arachidonic acid deficiency” has been reported before for RAW264.7 cells, MCF10a breast cancer cells, and HeLa cells [7, 16, 18]. Then we found in rapidly growing, 40% confluent tsA201 cells, that 38:4 is in fact dominant in the phosphoinositides, as it is in mammalian primary cells, and that the shift to shorter chain and less unsaturated fatty acids develops subsequently.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Surprisingly, transformed cell lines in culture, even though they are mammalian, have diminished 38:4 in their phosphoinositides. We showed this here for nearly confluent CHO and tsA201 cells (both having 36:1 and 36:2) [38], and a similar “arachidonic acid deficiency” has been reported before for RAW264.7 cells, MCF10a breast cancer cells, and HeLa cells [7, 16, 18]. Then we found in rapidly growing, 40% confluent tsA201 cells, that 38:4 is in fact dominant in the phosphoinositides, as it is in mammalian primary cells, and that the shift to shorter chain and less unsaturated fatty acids develops subsequently.…”
Section: Discussionmentioning
confidence: 67%
“…Altogether, with these methods, we achieved a detection limit below 20 pg (~20 fmole) injected into the MS machine. We have used these methods in several recent papers [3840]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may occur via delivery of PI4P to the ER by the transport activity of these proteins (Chung et al, 2015; Mesmin et al, 2013; Moser von Filseck et al, 2015) or, as proposed by others, by in trans action of Sac1 on the adjacent membrane (Dickson et al, 2016; Stefan et al, 2011). In yeast, deletion of the two VAP homologs (Scs2 and Scs22) results in strong PI4P elevations, with the bulk of excessive PI4P being localized at the plasma membrane (Stefan et al, 2011).…”
Section: Discussionmentioning
confidence: 93%
“…Finally, our modeling omits several significant cell-biological complexities that would compromise a desire for more perfect fits. Our previous work, as well as the work of others, shows that the four phosphoinositide species we have discussed actually have several dynamic pools on different membranes and organelles that exchange with each other by trafficking or lipid exchange in tens of seconds (38,39). Further, we and others have shown that when phosphoinositide pools are depleted by activating phospholipase C, the cellular lipid kinases are accelerated considerably (29,40).…”
Section: Discussionmentioning
confidence: 99%